"On the Network, off the Map": Developing Intervillage and Intragender Differentiation in Rural Water Supply. (April 2013) - Birkenholtz, Trevor
Despite decades of water-supply development programs in the Global South, their effect on gendered access to water remains both unclear and contradictory. This paper addresses this lacuna by examining the expansion of a rural water-supply network aimed at reducing household water scarcity in the arid zone of Rajasthan, India. Specifically, the Indira Gandhi Canal was conceived and constructed during the green revolution to 'green the Thar Desert'. But now, through a complex network of reservoirs, treatment facilities, distribution centers, and supply pipelines, it connects much of rural and urban western Rajasthan to a drinking water-supply network. The paper examines the interaction of water-supply technologies, social power relations and dynamic socioecological change operating within these development processes. To do so it draws on household surveys, interviews with water users and government engineers, and participant observation with women and children water collectors. The paper finds that this ongoing water development project rendered the water provision landscape technical on the surface, but that uneven flows of water between villages and people reveal a more complex water provision landscape. The expansion of the network based on a technical reimagining of water supply has resulted in intervillage scarcity, intragender differential access, usurious private water markets, the abandonment and then the proposed rehabilitation of traditional water bodies, and urban water logging. In the conclusion I argue for a rethinking of water-supply development programs through a political ecology approach that focuses on the emergent capacities of water-supply technologies to redirect existing socioecological associations in unanticipated ways. Looking at the relationship between nature—society and technology may illuminate the possible ruptures in these associations and the ways that they may be rearticulated to produce less differentiating modes of accessing water.